### (0) Obligation:

Runtime Complexity TRS:
The TRS R consists of the following rules:

O(0) → 0
+(0, x) → x
+(x, 0) → x
+(O(x), O(y)) → O(+(x, y))
+(O(x), I(y)) → I(+(x, y))
+(I(x), O(y)) → I(+(x, y))
+(I(x), I(y)) → O(+(+(x, y), I(0)))
*(0, x) → 0
*(x, 0) → 0
*(O(x), y) → O(*(x, y))
*(I(x), y) → +(O(*(x, y)), y)

Rewrite Strategy: FULL

### (1) DecreasingLoopProof (EQUIVALENT transformation)

The following loop(s) give(s) rise to the lower bound Ω(n1):
The rewrite sequence
+(I(x), I(y)) →+ O(+(+(x, y), I(0)))
gives rise to a decreasing loop by considering the right hand sides subterm at position [0,0].
The pumping substitution is [x / I(x), y / I(y)].
The result substitution is [ ].

### (3) RenamingProof (EQUIVALENT transformation)

Renamed function symbols to avoid clashes with predefined symbol.

### (4) Obligation:

Runtime Complexity Relative TRS:
The TRS R consists of the following rules:

O(0') → 0'
+'(0', x) → x
+'(x, 0') → x
+'(O(x), O(y)) → O(+'(x, y))
+'(O(x), I(y)) → I(+'(x, y))
+'(I(x), O(y)) → I(+'(x, y))
+'(I(x), I(y)) → O(+'(+'(x, y), I(0')))
*'(0', x) → 0'
*'(x, 0') → 0'
*'(O(x), y) → O(*'(x, y))
*'(I(x), y) → +'(O(*'(x, y)), y)

S is empty.
Rewrite Strategy: FULL

Infered types.

### (6) Obligation:

TRS:
Rules:
O(0') → 0'
+'(0', x) → x
+'(x, 0') → x
+'(O(x), O(y)) → O(+'(x, y))
+'(O(x), I(y)) → I(+'(x, y))
+'(I(x), O(y)) → I(+'(x, y))
+'(I(x), I(y)) → O(+'(+'(x, y), I(0')))
*'(0', x) → 0'
*'(x, 0') → 0'
*'(O(x), y) → O(*'(x, y))
*'(I(x), y) → +'(O(*'(x, y)), y)

Types:
O :: 0':I → 0':I
0' :: 0':I
+' :: 0':I → 0':I → 0':I
I :: 0':I → 0':I
*' :: 0':I → 0':I → 0':I
hole_0':I1_0 :: 0':I
gen_0':I2_0 :: Nat → 0':I

### (7) OrderProof (LOWER BOUND(ID) transformation)

Heuristically decided to analyse the following defined symbols:
+', *'

They will be analysed ascendingly in the following order:
+' < *'

### (8) Obligation:

TRS:
Rules:
O(0') → 0'
+'(0', x) → x
+'(x, 0') → x
+'(O(x), O(y)) → O(+'(x, y))
+'(O(x), I(y)) → I(+'(x, y))
+'(I(x), O(y)) → I(+'(x, y))
+'(I(x), I(y)) → O(+'(+'(x, y), I(0')))
*'(0', x) → 0'
*'(x, 0') → 0'
*'(O(x), y) → O(*'(x, y))
*'(I(x), y) → +'(O(*'(x, y)), y)

Types:
O :: 0':I → 0':I
0' :: 0':I
+' :: 0':I → 0':I → 0':I
I :: 0':I → 0':I
*' :: 0':I → 0':I → 0':I
hole_0':I1_0 :: 0':I
gen_0':I2_0 :: Nat → 0':I

Generator Equations:
gen_0':I2_0(0) ⇔ 0'
gen_0':I2_0(+(x, 1)) ⇔ I(gen_0':I2_0(x))

The following defined symbols remain to be analysed:
+', *'

They will be analysed ascendingly in the following order:
+' < *'

### (9) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
+'(gen_0':I2_0(n4_0), gen_0':I2_0(n4_0)) → *3_0, rt ∈ Ω(n40)

Induction Base:
+'(gen_0':I2_0(0), gen_0':I2_0(0))

Induction Step:
+'(gen_0':I2_0(+(n4_0, 1)), gen_0':I2_0(+(n4_0, 1))) →RΩ(1)
O(+'(+'(gen_0':I2_0(n4_0), gen_0':I2_0(n4_0)), I(0'))) →IH
O(+'(*3_0, I(0')))

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (11) Obligation:

TRS:
Rules:
O(0') → 0'
+'(0', x) → x
+'(x, 0') → x
+'(O(x), O(y)) → O(+'(x, y))
+'(O(x), I(y)) → I(+'(x, y))
+'(I(x), O(y)) → I(+'(x, y))
+'(I(x), I(y)) → O(+'(+'(x, y), I(0')))
*'(0', x) → 0'
*'(x, 0') → 0'
*'(O(x), y) → O(*'(x, y))
*'(I(x), y) → +'(O(*'(x, y)), y)

Types:
O :: 0':I → 0':I
0' :: 0':I
+' :: 0':I → 0':I → 0':I
I :: 0':I → 0':I
*' :: 0':I → 0':I → 0':I
hole_0':I1_0 :: 0':I
gen_0':I2_0 :: Nat → 0':I

Lemmas:
+'(gen_0':I2_0(n4_0), gen_0':I2_0(n4_0)) → *3_0, rt ∈ Ω(n40)

Generator Equations:
gen_0':I2_0(0) ⇔ 0'
gen_0':I2_0(+(x, 1)) ⇔ I(gen_0':I2_0(x))

The following defined symbols remain to be analysed:
*'

### (12) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
*'(gen_0':I2_0(n40533_0), gen_0':I2_0(0)) → gen_0':I2_0(0), rt ∈ Ω(1 + n405330)

Induction Base:
*'(gen_0':I2_0(0), gen_0':I2_0(0)) →RΩ(1)
0'

Induction Step:
*'(gen_0':I2_0(+(n40533_0, 1)), gen_0':I2_0(0)) →RΩ(1)
+'(O(*'(gen_0':I2_0(n40533_0), gen_0':I2_0(0))), gen_0':I2_0(0)) →IH
+'(O(gen_0':I2_0(0)), gen_0':I2_0(0)) →RΩ(1)
+'(0', gen_0':I2_0(0)) →RΩ(1)
gen_0':I2_0(0)

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (14) Obligation:

TRS:
Rules:
O(0') → 0'
+'(0', x) → x
+'(x, 0') → x
+'(O(x), O(y)) → O(+'(x, y))
+'(O(x), I(y)) → I(+'(x, y))
+'(I(x), O(y)) → I(+'(x, y))
+'(I(x), I(y)) → O(+'(+'(x, y), I(0')))
*'(0', x) → 0'
*'(x, 0') → 0'
*'(O(x), y) → O(*'(x, y))
*'(I(x), y) → +'(O(*'(x, y)), y)

Types:
O :: 0':I → 0':I
0' :: 0':I
+' :: 0':I → 0':I → 0':I
I :: 0':I → 0':I
*' :: 0':I → 0':I → 0':I
hole_0':I1_0 :: 0':I
gen_0':I2_0 :: Nat → 0':I

Lemmas:
+'(gen_0':I2_0(n4_0), gen_0':I2_0(n4_0)) → *3_0, rt ∈ Ω(n40)
*'(gen_0':I2_0(n40533_0), gen_0':I2_0(0)) → gen_0':I2_0(0), rt ∈ Ω(1 + n405330)

Generator Equations:
gen_0':I2_0(0) ⇔ 0'
gen_0':I2_0(+(x, 1)) ⇔ I(gen_0':I2_0(x))

No more defined symbols left to analyse.

### (15) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
+'(gen_0':I2_0(n4_0), gen_0':I2_0(n4_0)) → *3_0, rt ∈ Ω(n40)

### (17) Obligation:

TRS:
Rules:
O(0') → 0'
+'(0', x) → x
+'(x, 0') → x
+'(O(x), O(y)) → O(+'(x, y))
+'(O(x), I(y)) → I(+'(x, y))
+'(I(x), O(y)) → I(+'(x, y))
+'(I(x), I(y)) → O(+'(+'(x, y), I(0')))
*'(0', x) → 0'
*'(x, 0') → 0'
*'(O(x), y) → O(*'(x, y))
*'(I(x), y) → +'(O(*'(x, y)), y)

Types:
O :: 0':I → 0':I
0' :: 0':I
+' :: 0':I → 0':I → 0':I
I :: 0':I → 0':I
*' :: 0':I → 0':I → 0':I
hole_0':I1_0 :: 0':I
gen_0':I2_0 :: Nat → 0':I

Lemmas:
+'(gen_0':I2_0(n4_0), gen_0':I2_0(n4_0)) → *3_0, rt ∈ Ω(n40)
*'(gen_0':I2_0(n40533_0), gen_0':I2_0(0)) → gen_0':I2_0(0), rt ∈ Ω(1 + n405330)

Generator Equations:
gen_0':I2_0(0) ⇔ 0'
gen_0':I2_0(+(x, 1)) ⇔ I(gen_0':I2_0(x))

No more defined symbols left to analyse.

### (18) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
+'(gen_0':I2_0(n4_0), gen_0':I2_0(n4_0)) → *3_0, rt ∈ Ω(n40)

### (20) Obligation:

TRS:
Rules:
O(0') → 0'
+'(0', x) → x
+'(x, 0') → x
+'(O(x), O(y)) → O(+'(x, y))
+'(O(x), I(y)) → I(+'(x, y))
+'(I(x), O(y)) → I(+'(x, y))
+'(I(x), I(y)) → O(+'(+'(x, y), I(0')))
*'(0', x) → 0'
*'(x, 0') → 0'
*'(O(x), y) → O(*'(x, y))
*'(I(x), y) → +'(O(*'(x, y)), y)

Types:
O :: 0':I → 0':I
0' :: 0':I
+' :: 0':I → 0':I → 0':I
I :: 0':I → 0':I
*' :: 0':I → 0':I → 0':I
hole_0':I1_0 :: 0':I
gen_0':I2_0 :: Nat → 0':I

Lemmas:
+'(gen_0':I2_0(n4_0), gen_0':I2_0(n4_0)) → *3_0, rt ∈ Ω(n40)

Generator Equations:
gen_0':I2_0(0) ⇔ 0'
gen_0':I2_0(+(x, 1)) ⇔ I(gen_0':I2_0(x))

No more defined symbols left to analyse.

### (21) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
+'(gen_0':I2_0(n4_0), gen_0':I2_0(n4_0)) → *3_0, rt ∈ Ω(n40)